Evaluation of Borewell Water of Various Places Located in and around Virudhunagar - Raman, N.; Murugesan, A. (Asian Journal of Chemistry, 2010)
The suitability of water for drinking purpose is studied by collecting samples from the places located in and around Virudhunagar. The physico-chemical parameters of the above samples indicate that the drinking water is not so much polluted. Some of the samples have TDS, hardness, sulphate, calcium and magnesium values exceeding the permissible limits for drinking purposes. It is observed that the main sources of pollution are due to waste water industries, municipal sewage, lack of sanitation, presence of inorganic constituents in waste water.